Meta-analysis of studies of occupational exposure to vinyl chloride in relation to cancer mortality - Boffetta, Paolo; Matisane, Linda; Mundt, Kenneth A.; Dell, Linda D. (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'A meta-analysis was made of studies addressing occupational exposure to vinyl chloride in relation to cancer mortality. ' ' METHODS ': 'Two recently updated multicenter cohort studies and six smaller studies were identified. For selected neoplasms, standardized mortality ratios (SMR) and 95% confidence intervals (95% CI) were abstracted (or calculated from raw data). In cases of lack of heterogeneity (P-value ≥0.1), meta-analyses were conducted using a random-effects model. ' ' RESULTS ': 'With SMR values ranging from 1.63 to 57.1, all six studies for which these ratios could be obtained suggested an increased risk of liver cancer. For four of these studies, excesses persisted when known cases of angiosarcoma of the liver (ASL) were excluded. The meta-SMR for liver cancers other than ASL (based on the 2 large cohorts) was 1.35 (95% CI 1.04-1.77). The meta-SMR for lung cancer was 0.90 (95% CI 0.77-1.00, based on 5 studies), although higher SMR values were reported in early studies. The meta-SMR for brain cancer, based on 5 studies, was 1.26 (95% CI 0.98-1.62). For soft tissue sarcomas, the meta-SMR based on 4 studies was 2.52 (95% CI 1.56-4.07). The meta-SMR for lymphatic and hematopoietic neoplasms in the 2 large studies was 0.90 (95% CI 0.75-1.01), although 3 of the smaller studies reported significant excesses. ' ' CONCLUSIONS ': 'Apart from the known risk of ASL, workers exposed to vinyl chloride may experience an increased risk of hepatocellular carcinoma and soft-tissue sarcoma; however, these results may have been influenced by the underdiagnosis of true ASL. Increased mortality from lung and brain cancers and from lymphatic and hematopoietic neoplasms cannot be excluded; mortality from other neoplasms does not appear to be increased.
Keywords: angiosarcoma of the liver; brain cancer; cancer mortality; hematopoietic neoplasms; liver cancer; lung cancer; meta-analysis; occupational exposure; vinyl chloride